Facile phase transfer of hydrophobic Fe3O4@Cu2−xS nanoparticles by red blood cell membrane for MRI and phototherapy in the second near-infrared window. Issue 6 (16th January 2020) - Lin, Kecan; Cao, Yanbing; Zheng, Dongye; Li, Qin; Liu, Hui; Yu, Peiwen; Li, Jiong; Xue, Yanan; Wu, Ming
Abstract : Theranostic agents for MRI and NIR II phototherapy by using red blood cell membrane for phase transfer of Fe3 O4 @Cu2− x S nanoparticles. Abstract : The development of nanotheranostic agents integrating diagnosis and therapy has gained tremendous attention in the past few decades, but many of them are inherently hydrophobic and need complicated phase-transfer and tedious surface modifications. This work proposed a facile method of transferring hydrophobic Fe3 O4 @Cu2− x S nanoparticles from oil to water by using red blood cell membrane to create theranostic nanobeads for T 2 -weighted MRI and second near-infrared photothermal ablation. The obtained nanoplatform, namely SCS@RBCM, showed a core–shell structure with the inner core densely packed with Fe3 O4 @Cu2− x S nanoclusters and the surface coated with a layer of RBCM. SCS@RBCM displayed a stable nanostructure, high NIR II light absorption and photothermal conversion ability, T 2 -weighted MR imaging and magnetic field targeting ability. Meanwhile, the RBCM cloaking endowed SCS with reduced elimination by macrophages. With the navigation of an external magnetic field (MF), the tumor accumulation of SCS@RBCM was dramatically increased, thus achieving good performance of MR imaging and antitumor efficacy through the PTT effect under NIR II irradiation. Therefore, our strategy presents a new and desirable paradigm in the phase-transfer of hydrophobic nanotheranostics for optimizing their biomedical performance.